Pengaruh Brand Awareness, Brand Image, dan Marketing Mix terhadap Purchase Intention Kopi Bubuk Lokal di Bali - Gaus Gunawan; Keni Keni (Universitas Tarumanagara, 2022)
This study aims to analyze the effect of Brand Awareness, Brand Image, and Marketing Mix variables on Purchase Intention. This type of research is descriptive with a cross-sectional approach. The sample used as the respondent is a local ground coffee drinker in Bali, while the number of respondents was 160 respondents from a total of 179 respondents who answered the questionnaires that had been distributed. The data analysis technique used in this study was Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS software (3.3.3). Data analysis of this research was carried out in three stages, namely: an outer model analysis, inner model analysis, and hypothesis submission. Based on the results of the study, it was found that there was an insignificant positive effect of brand awareness on purchase intention, and there was a significant positive effect of brand image and marketing mix on purchase intention. Penelitian ini bertujuan untuk menganalisis pengaruh variabel Brand Awareness, Brand Image, dan Marketing Mix terhadap Purchase Intention. Jenis penelitian ini deskriptif dengan pendekatan cross-sectional. Sampel yang dijadikan responden adalah peminum kopi bubuk lokal di Bali, adapun jumlah responden sebanyak 160 responden dari total 179 responden yang menjawab kuesioner yang telah disebarkan. Teknik analisis data yang digunakan dalam penelitian ini yaitu Partial Least Squares-Structural Equation Modeling (PLS-SEM) dengan menggunakan software SmartPLS (3.3.3). Analisis data penelitian ini dilakukan dalam tiga tahap yaitu: analisis outer model, analisis inner model, dan pengajuan hipotesis. Berdasarkan hasil penelitian, ditemukan bahwa terdapat pengaruh positif tidak signifikan brand awareness terhadap purchase intention, dan terdapat pengaruh positif signifikan brand image dan marketing mix terhadap purchase intention.